Case Report: Re-Emergence of Rabies Cases in Denpasar - Praptikaningtyas, Anak Agung Istri; Widiastuti, Priska (Publikasi Indonesia, 2025)
Rabies is a fatal zoonotic disease caused by Lyssavirus from the Rhabdoviridae family, which primarily affects the central nervous system. Once symptoms manifest, the case fatality rate exceeds 99%, making it one of the deadliest viral infections. The high mortality rate emphasizes the urgency of preventive measures. This case report aims to highlight the clinical features, diagnostic challenges, and management of symptomatic rabies in humans and reinforce the importance of Post-Exposure Prophylaxis (PEP). A descriptive clinical case report is presented of a 41-year-old male who developed rabies symptoms three months after a dog bite, having not received PEP. Clinical presentation included hydrophobia, vomiting, restlessness, and paresthesia. The patient was treated symptomatically with intravenous antibiotics, antipyretics, gastric protection, and psychiatric support, alongside monitoring in a special care unit. The results show that despite comprehensive symptomatic management—including ceftriaxone, paracetamol, omeprazole, and haloperidol rabies remained untreatable at the symptomatic stage. This case underscores the critical window for prevention before the onset of symptoms. Rabies remains incurable once neurological symptoms appear. Thus, in any suspected exposure to potentially rabid animals, prompt and complete post-exposure prophylaxis comprising wound care, anti-rabies vaccine, and rabies immunoglobulin is essential. This case reinforces the public health importance of early intervention to prevent fatal outcomes.